Bioethical principles and their application against Hepatitis B virus infection (Research, Society and Development, 2022)
Bioethics has the function of ensuring the well-being of people, guaranteeing and avoiding possible damages that may occur to their interests, providing the professional and those who are served by him, the right to respect and will, respecting their beliefs and values. Objective: to highlight the bioethical principles and their application against Hepatitis B virus infection in the light of the literature. Methods; This is a review of mixed studies, published in the bases of the National Library of Medicine (PUBMED), Latin American and Caribbean Literature on Health Sciences (LILACS) and Scientific Electronic Library Online (SCIELO), in the chronological period between 2012 to 2022. Results: It was evidenced that chronic HBV infection is the main cause of Liver Cirrhosis and hepatocellular carcinoma and that vaccination is an effective way to change this scenario. The vaccine contemplates the bioethical principle of justice and scientific evidence supports beneficence, however, adverse effects interfere with non-maleficence. However, side effects result in conflicts involving the principle of non-maleficence. These consequences are intensified when they are associated with individual and/or collective factors, which can interfere with the individual's autonomy in adhering to such a prevention measure. Conclusion: The treatment and prevention of Hepatitis B should be widely discussed in association with bioethical principles, developing health actions that can guarantee the individual the principles of autonomy, beneficence, non-maleficence and justice.